The Limitations and Legitimacy of Judges in Filling Legal Vapor Amidst Demand for Progressive Legal Reform - Hary Kesowo Wibowo; KMS Herman (Indonesian Journal Publisher, 2026)
This study aims to analyze the limitations and legitimacy of judges in filling the legal vacuum amidst demands for progressive legal reform in the Indonesian legal system. The legal vacuum (rechtvacuum) is a consequence of societal dynamics that cannot always be balanced by the formation of laws and regulations. In this context, judges have a constitutional and legal obligation to continue examining and deciding cases as mentioned in both Article 24 paragraph (1) of the Republic of Indonesia's 1945 Constitution and Article 5 paragraph (1) and Article 10 paragraph (1) of Law Number 48 of 2009 respecting Judicial Power. This research employs a statutory and conceptual approach using a normative legal strategy. The results of the study indicate that legal discovery (rechtsvinding) is an obligation of judges as a consequence of the principle of ius curiae novit and the principle of the rule of law. However, the expansion of the role of judges within a progressive legal framework must remain within constitutional limits by respecting the system of checks and balances and the idea of separation of powers. The legitimacy of judges in filling legal gaps is determined by a clear normative basis, rational and systematic legal argumentation, and an orientation toward protecting constitutional rights and substantive justice. Thus, the progressive role of judges can contribute to national legal reform without exceeding legislative authority.